Optimalisasi Posyandu Remaja dalam Pencegahan Anemia pada Remaja Putri - Widhi Astuti, KH Endah; Rosalinna, Rosalinna (Jurnal Pengabdian kepada Masyarakat (ABDIKEMAS), 2024)
Anemia in adolescent girls is a global health issue that impacts quality of life and future reproductive health. This community service program aimed to improve knowledge, attitudes, and hemoglobin levels among adolescent girls through optimizing youth health posts (Posyandu Remaja) in Jetis Jaten Village, Karanganyar. The program involved 38 participants and was conducted over three months using interactive education, simulations, and mentoring methods. Results showed an 88.9% increase in knowledge, a 105% improvement in dietary awareness, and a reduction in anemia prevalence from 73.7% to 34.2%. This program demonstrated that a community-based approach through youth health posts is effective in preventing anemia and can serve as a sustainable model for public health development..